Design of Multi-Functional Superhydrophobic Coating via Bacterium-Induced Hierarchically Structured Minerals on Steel Surface - Yiwen Zhang; Tao Liu; Jian Kang; Na Guo; Zhangwei Guo; Jinghao Chen; Yansheng Yin (Frontiers in Microbiology, 2022)
The fabrication of an eco-friendly, multi-functional, and mechanically robust superhydrophobic coating using a simple method has many practical applications. Here, inspired by shell nacre, the micro- or nano-scale surface roughness that is necessary for superhydrophobic coatings was formed via Bacillus subtilis–induced mineralization. The biomineralized film coated with hexadecyltrimethoxysilane (HDTMS) exhibited superhydrophobicity with water contact angles of 156°. The biomimetic HDTMS/calcite-coating showed excellent self-cleaning, anti-icing, and anti-corrosion performances. Furthermore, mechanically robust superhydrophobicity could be realized by hierarchically structured biomineralized surfaces at two different length scales, with a nano-structure roughness to provide water repellency and a micro-structure roughness to provide durability. Our design strategy may guide the development of “green” superhydrophobic coatings that need to retain effective multi-functional abilities in harsh marine environments.